On the Solution of a Physics Problem of ’Moment of Inertia’ - Chattopadhyay, Rabindranath (Indian Science Cruiser, 2018)
A problem, usually given sometimes in various entrance examination, from the chapter of rotational motion of rigid body, is considered here and a brief critical analysis of the same is presented in this article.